Explaining the black box: HPWS and organisational climate. Issue 5 (3rd August 2015) - Cafferkey, Kenneth; Dundon, Tony
Abstract : Purpose: – The purpose of this paper is to test the relationship between human resource practices (HRP) and employee outcomes at two distinct levels of analysis. While significant evidence exists as to the occurrence of a relationship, the mechanisms and process through which this happens remain largely unexplored. This paper aims to test the impact of organisational climate (OC) as a mediating mechanism between HRP and employees' outcomes as the expected routed to organisational performance. Design/methodology/approach: – The paper uses two related surveys to test the research propositions at two different levels. First a macro management-based survey of multiple top performing organisations provides the basis for locating a suitable case organisation to test the same propositions using an employee-based survey. Findings: – The findings indicate that OC is shown to be an important and neglected mediating factor in the causal relationship between HR and employee outcomes. The findings also indicate that the strength of the relationship is dependent on the level of analysis employed. Originality/value: – The originality/value of the findings argue that employees are better placed to report on items such as the impact of human recourse management practice and OC outcomes on performance indicators over and above their managerial counterparts.